Structural characterization of HDAC2-MTA1 complex - Gautam, Narayan; Adhikari, Narayan Prasad (BIBECHANA, 2025)
Histone deacetylases are recruited to specific transcriptional repression complexes through interactions with corepressor proteins. This recruitment leads to chromatin condensation and transcriptional silencing. In this study, we modeled the complex structure of HDAC2 with MTA1 and investigated the HDAC2 and MTA1 interactions using all-atom molecular dynamics (MD) simulation. Our results show that the ELM2-SANT domains of MTA1 wrap completely around HDAC2. We identified the different types of interactions such as hydrogen bonds, salt bridges, and hydrophobic interactions. Specifically, GLU186, GLU147, GLU163, LYS166, and LYS124 amino acid residues of HDAC2 form both hydrogen bond and salt bridge interactions with ARG168, ARG189, ASP187, and GLU195 amino acid residues of MTA1. Additionally, TYR15 amino acid of HDAC2 form hydrogen bonds with GLU195 amino acid of MTA1. In addition to hydrogen bond and salt bridge interactions, we also analyzed hydrophobic interaction.